Johor Asia latitude one - Guariglia, Justin 1974- (de.Mo design, 2011)
What happens when a modern day princess asks National Geographic photographer Justin Guariglia and veteran Wall Street Journal reporter John Krich to chronicle and capture all the color and complexities of a critical, yet little-known corner of the Orient? The stunning result is Johor: Asia Latitude One, offering hours of pleasure for armchair explorers and a rare view of a magical realm's remarkable variety of humanity. Packaged by de.MO's acclaimed graphic designer Giorgio Baravalle in a contemporary style, this gem of photojournalism is plucked from the sun-lit balm of a realm whose very name means, "jewel land.